2020
DOI: 10.1089/neu.2019.6905
|View full text |Cite
|
Sign up to set email alerts
|

FTY720 Attenuates Neuropathic Pain after Spinal Cord Injury by Decreasing Systemic and Local Inflammation in a Rat Spinal Cord Compression Model

Abstract: Neuropathic pain severely impairs rehabilitation and quality of life after spinal cord injury (SCI). The sphingosine-1phosphate receptor agonist, FTY720, plays an important protective role in neuronal injury. This study aims to examine the effects of FTY720 in a rat acute SCI model, focusing on neuropathic pain. Female rats with SCI induced by 1-min clip compression were administered vehicle or 1.5 mg/kg of FTY720 24 h after the injury. Using the mechanical nociceptive threshold test, we monitored neuropathic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…Both inhibition of ceramide biosynthesis [95] and FTY720 administration shortly after spinal contusion ameliorate injury outcomes and promote functional recovery [96]. Recently, a study revealed that FTY720 reduces spinal cord injury-induced neuropathic pain by dampening neuroinflammation and inhibiting glial scar formation [97].…”
Section: S1p Axis In Central Sensitizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Both inhibition of ceramide biosynthesis [95] and FTY720 administration shortly after spinal contusion ameliorate injury outcomes and promote functional recovery [96]. Recently, a study revealed that FTY720 reduces spinal cord injury-induced neuropathic pain by dampening neuroinflammation and inhibiting glial scar formation [97].…”
Section: S1p Axis In Central Sensitizationmentioning
confidence: 99%
“…Unlike paclitaxel and oxaliplatin, S1PR1-based therapies do not block bortezomib-induced neuropathic pain in female rats and mice 2019 [111] Ceramide-induced pain behaviors in mice involve NLRP2 inflammasome activation in the DRG 2019 [50] Activation of S1PR1 in spinal astrocytes, following intrathecal injection of SEW2871, leads to NLRP3 inflammasome activation, IL-1β production, and pain behaviors in mice and rats 2019 [81] Functional and competitive S1PR1 antagonists block traumatic nerve injury-induced neuropathic pain in mice and rats. S1PR1 expressed on astrocytes is identified as a target for therapeutic intervention with S1PR1 antagonists 2019 [84] S1PR2 activation in spinal cord attenuates neuropathic pain and neuroinflammation in a model of traumatic nerve injury in rats 2019 [91] Clinical trials for proof of concept in patients with breast cancer have begun with fingolimod to explore efficacy in preventing and/or treating chemo-induced neuropathic pain (NCTID: NCT03941743; NCT03943498) 2019 i FTY720 ameliorates spinal cord injury induced-neuropathic pain in rats by dampening neuroinflammation and inhibiting glial scar formation 2020 [97] Role for S1PR1 in opioid-mediated adverse events is identified. Functional and competitive S1PR1 antagonists block morphine-induced hyperalgesia, tolerance, and dependence 2020 [83] Activation of S1PR2 following systemic administration of the selective S1PR2 agonist CYM-5478 attenuates cisplatin-induced neuropathic pain in rats 2020 [34] Patients with CINP have single nucleotide polymorphisms (SNPs) in a genomic region that regulate S1PR1 gene expression.…”
Section: Disclaimer Statementmentioning
confidence: 99%
“…The method for inducing SCI has been previously reported. [29][30][31] Briefly, one-minute compression by modified aneurysm clip (Mizuho, Tokyo, Japan) was used to induce thoracic SCI. The clip was designed to have 30 g closing force, and the blade was smoothened for applying equal pressure to the spinal cord.…”
Section: Experimental Animalsmentioning
confidence: 99%
“…Tacrolimus, also known as FK506, is another macrolide that is widely used as an immunosuppressive medication [84,88]. It can cross the brain–blood barrier and exert robust neuroprotective and neuroregenerative effects in different CNS diseases such as SCI ( Table 1 ) [1,89–95]. Tacrolimus promotes neuroprotection in addition to neural and axonal regeneration associated with functional recovery in SCI rodents [96–100].…”
Section: Antibiotics With Therapeutic Effects In Scimentioning
confidence: 99%
“…This effect is mediated by inhibiting calcineurin [96–100], increasing neuronal growth‐associated protein (GAP)‐43 levels [91], inhibiting iNOS and superoxide radicals, preventing mitochondrial dysfunction and neuronal apoptosis signaling [101–103], inhibiting caspase 3 activity, and finally attenuating oligodendroglia apoptosis ( Figure ) [104]. Other mechanisms underlying such effects of tacrolimus on SCI include attenuating invasion of pro‐inflammatory cells (e.g., macrophages) into the injured sites [105], decreasing glial fibrillary acidic protein (GFAP), COX‐2, and pro‐inflammatory cytokines (e.g., IL‐1β) levels [101], as well as inhibiting nuclear factor kappa B (NF‐kB) activation in microglia [90,93]. López‐Vales et al also found that daily administration of tacrolimus at nonimmunosuppressive doses can boost the neuroprotective and neuroregenerative effects of olfactory ensheathing cell (OEC) grafts in spinal cord lesions, though the underlying mechanism is yet to be identified in this model [106].…”
Section: Antibiotics With Therapeutic Effects In Scimentioning
confidence: 99%